(untitled) (American Journal of Islam and Society, 1994)
Introduction This paper is a report on the state of research in two areas of Islamic studies: Islam and economics and Islam and governance. I researched and wrote it as part of my internship at the Ford Foundation during the summer of 1992. On Discourse. The study of Islam in the United States has moved far beyond the traditional historical and philological methods. This is perhaps best explained by the development of analytically rigorous social science methods that have contributed to a better balance between the humanistic concerns of the more traditional approaches and efforts at systematizing the study of Islam and classifying it across boundaries of communities, religions, even epochs. This is said to have s t a d with the development of irenic attitudes towards Islam, which changed the direction of westem orientalist writings from indifference (at best) and often open hostility to and contempt of Islamic values (however they were understood) to phenomenological works by scholars who saw the study of Islam as something to be taken seriously and for its own sake, which is best exemplified by Clifford Geertz’s Islam Observed. The work of Edward Said contested this evolution, and the publication of his Orientalism has been described as "a stick of dynamite"’ that, despite its impact in mobilizing a reevaluation of the field, was unwarranted in its pessimism. In any case, the field has continued to evolve, with the most powerful force moving it being the subject itself. The phenomenological/orientalist approach, if we can point to one today, ...